LEDs with Organized InGaN Nanopylons Generating within Green, Yellow, as well as Blue Region - Phan Xuan Le; Nguyen Huy Khiem (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
The creation of structured settings for InGaN/GaN (I/G) nano-pylon diodes emit illumination (LED) within the green, yellow, as well as blue (GYB) spectrum regions using molecular beam epitaxy has been described. Compared with InGaN (planar) sheets of identical structure and thickness, the gadget’s working area, including one nano-pylon InGaN part for titularly identical element as well as lengthiness between 250 and 500 nm, would be unaffected by prolonged problems. Electroluminescent hue ranges indicate a minor blue change with rising power (nearly non-existent in the yellow gadget) and line wideness that are marginally wider than those of modern InGaN quantum wells. InGaN was also utilized in a phosphor-transmuted white LED (WLED) to enhance its optical attributes such as scattering, lumen, and color rendition. It was found that InGaN has its own advantages and limitations. It was found that adjusting the InGaN discharge to 460 nm would benefit the lumen and color rendition of the WLED under a particle size of 9 µm, while a 450-nm discharge would promote scattering, both of which better match the human sight.